2021
DOI: 10.3389/fmed.2021.679487
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities of Patients With Idiopathic Pulmonary Fibrosis in Four Latin American Countries. Are There Differences by Country and Altitude?

Abstract: Background: Comorbidities in idiopathic pulmonary fibrosis (IPF) affect quality of life, symptoms, disease progression and survival. It is unknown what are the comorbidities in patients with IPF in Latin America (LA) and if there are differences between countries. Our objective was to compare IPF comorbidities in four countries and analyze possible differences by altitude.Methods: Patients with IPF according 2012 ATS/ERS/JRS/ALAT guidelines, from two cities with an altitude of ≥2,250 m: Mexico City (Mexico) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Estimates of comorbidity prevalence vary widely between studies, but the rates of multiple prevalent comorbidity identified in our study are in line with those documented in prior registry studies [ 9 , 27 ]. Regarding individual comorbidities, previous studies have generated comparable estimates of the prevalence of hypertension [ 9 , 28 ], cardiac disease [ 9 , 27 ], thyroid disease [ 27 ], GERD [ 9 ], cerebrovascular disease [ 10 ], heart failure [ 10 ] in IPF populations (Table 1 ). The prevalence of diabetes was lower in our IPF cohort than prior studies (11% versus 23–45%) [ 9 , 10 , 29 ], but depression was more commonly seen in our study than in prior reports (23% versus 3–15%) [ 9 , 10 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of comorbidity prevalence vary widely between studies, but the rates of multiple prevalent comorbidity identified in our study are in line with those documented in prior registry studies [ 9 , 27 ]. Regarding individual comorbidities, previous studies have generated comparable estimates of the prevalence of hypertension [ 9 , 28 ], cardiac disease [ 9 , 27 ], thyroid disease [ 27 ], GERD [ 9 ], cerebrovascular disease [ 10 ], heart failure [ 10 ] in IPF populations (Table 1 ). The prevalence of diabetes was lower in our IPF cohort than prior studies (11% versus 23–45%) [ 9 , 10 , 29 ], but depression was more commonly seen in our study than in prior reports (23% versus 3–15%) [ 9 , 10 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences in saturation can be explained by altitude. Due to Bogotá’s location at 2,640 m above sea level, PaO 2 is around 60 mmHg and SaO 2 is 90% in normal patients, with significant desaturations during exercise in patients with interstitial lung disease ( 11 ). Despite these lower saturations at altitude, different studies suggest that this does not represent a negative impact on the mortality of patients with COVID-19 residing at high altitudes ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…At altitude, due to lower barometric pressure and lower inspired pressure of oxygen, there are lower levels of arterial oxygen pressure and saturation in both normal subjects and patients with respiratory disease ( 10 , 11 ). More than 80 million people in the world live 2,500 m above sea level, mainly in Latin America and the Andean region ( 12 ).…”
Section: Introductionmentioning
confidence: 99%